Strain rate dependence of dynamic recrystallization and texture evolution in hot compressed Mg-Gd-Er-Zr alloy - Ning Ding; Wenbo Du; Shubo Li; Ke Liu; Xian Du; Zijian Yu (Journal of Magnesium and Alloys)
Hot deformation with high strain rate has been paid more attention due to its high efficiency and low cost, however, the strain rate dependent dynamic recrystallization (DRX) and texture evolution in hot deformation process, which affect the formability of metals, are lack of study. In this work, the DRX behavior and texture evolution of Mg-8Gd-1Er-0.5Zr alloy hot compressed with strain rates of 0.1 s−1, 1 s−1, 10 s−1 and 50 s−1 are studied, and the corresponding dominant mechanisms for DRX and texture weakening are discussed. Results indicated the DRX fraction was 20% and the whole texture intensity was 16.89 MRD when the strain rate was 0.1 s−1, but they were 76% and 6.55 MRD, respectively, when the strain rate increased to 50 s−1. The increment of DRX fraction is suggested to result from the reduced DRX critical strain and the increased dislocation density as well as velocity, while the weakened whole texture is attributed to the increased DRX grains. At the low strain rate of 0.1 s−1, discontinuous DRX (DDRX) was the dominant, but the whole texture was controlled by the deformed grains with the preferred orientation of {0001}⊥CD, because the number of DDRX grains was limited. At the high strain rate of 50 s−1, continuous DRX (CDRX) and twin-induced DRX (TDRX) were promoted, and more DRX grains resulted in orientation randomization. The whole texture was mainly weakened by CDRX and TDRX grains, in which CDRX plays a major role. The results of present work are significant for understanding the hot workability of Mg-RE alloys with a high strain rate.